PERKEMBANGAN TEORI KONSTITUSI UNTUK MENDUKUNG NEGARA KESATUAN REPUBLIK INDONESIA - Erry Gusman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Constitution is a basic law that is used as a guideline in the administration of a country. The constitution can be in the form of a written basic law commonly referred to as the Constitution and may also be unwritten. In simple terms, the constitution can be defined as a number of legal provisions arranged systematically to organize and regulate the main structure and function of government institutions, including matters concerning the authority of those institutions. In a narrower sense, the constitution is even interpreted as a document that contains the legal provisions. A unitary state is a country which is not composed of several countries, as in a federated country, but the country is single, meaning that there is only one country, there is no state in the country. So thus, there is only one government in the unitary state, namely the central government which has the highest power or authority in all fields of government. It is this central government which at the last and highest level can decide everything in the unitary State.